MODEL PENGEMBANGAN LEARNING COMMUNITY DALAM PEMBELAJARAN BAHASA INGGRIS TERHADAP PENINGKATKAN PRESTASI BELAJAR SISWA - Muchsin, Muchsin (Universitas Islam Negeri Raden Intan Lampung, 2016)
One of learning model which need to beconsidered by educators is a model learningcommunity method, namely talking and sharingexperiences each others, cooperating each otherand creating enhanced learning than by self wherestudents were placed as a subject of study. Inaddition, students also make the processmeaningful activity, where students discuss withtheir friends or sharing information among themand asking the teacher to guide on a subject wherethe teaching materials are considered difficulty, sothe process of learning more effective andmotivate, This research is the development ofcommunity learning models in learning English toincrease student achievement at SMP Banda Acehand Aceh Besar. The Results of the study wascommunity learning model can improve theEnglish language skills and students’ achievementsthrough training as continuously, systematic andimplemented in school and society